URGENSI DAKWAH PEMBERDAYAAN MASYARAKAT DI ERA INDUSTRY 4.0 - Ainur Rofiq (Indonesian Journal of Islamic Communication, 2020)
Community empowerment is part of da’wah activities which are often interpreted as oral activities. Da'wah in the form of community empowerment activities is known as Da'wah billhal. Preaching by action (bilhal) is not only aimed at improving the quality of your faith, but also as an effort to improve the standard of life of the people as mad'u. Improving the standard of living of the community can be done with empowerment patterns. In tune with the paradigm of community empowerment, that preaching has the aim to change the situation of honey through economic, social, political, cultural, educational, health and so forth. Community empowerment positions madu as both subject and object in da'wah activities. In the Islamic perspective community empowerment has a noble goal of eliminating socioeconomic gaps between one another. So that in Islam the principles of social justice are taught, the principle of equality, the principle of participation, the principle of respect for the work ethic, and the principle of help. There are two ways taken in Islam in community empowerment, namely consumer empowerment that is consumptive and community empowerment that is productive.